Food anticipation in Bmal1-/- and AAV-Bmal1 rescued mice: a reply to Fuller et al - Mistlberger Ralph E; Buijs Ruud M; Challet Etienne; Escobar Carolina; Landry Glenn J; Kalsbeek Andries; Pevet Paul; Shibata Shigenobu (Journal of Circadian Rhythms, 2009)
Abstract Evidence that circadian food-anticipatory activity and temperature rhythms are absent in Bmal1 knockout mice and rescued by restoration of Bmal1 expression selectively in the dorsomedial hypothalamus was published in 2008 by Fuller et al and critiqued in 2009 by Mistlberger et al. Fuller et al have responded to the critique with new information. Here we update our critique in the light of this new information. We also identify and correct factual and conceptual errors in the Fuller et al response. We conclude that the original results of Fuller et al remain inconclusive and fail to clarify the role of Bmal1 or the dorsomedial hypothalamus in the generation of food-entrainable rhythms in mice.